A comparative study of the management of pediatric femoral shaft fractures treated conservatively with traction or spica casting - Shakya, Akash; Kakadiya, Ghanshyam; Soni, Yogesh; Garje, Vinayak (International Journal of Research in Orthopaedics, 2020)
Background: Femoral shaft fractures, though not very common, are of major concern for orthopedic surgeons. the management for infants and older children is generally universal but the young patients still offer a management dilemma. Methods: We present a prospective study conducted at a tertiary care hospital in India of 37 children between 1 year and 6 years to compare the two conservative methods most commonly used i.e. spica casting and traction application. Results: We found that though both the methods are similar in the time for union, shortening was better controlled with traction and angulation with spica casting. The frequency of other complications was also comparable. Conclusions: Both the methods give acceptable results and given the feasibility of such procedures in developing countries, both may be recommended. However, the choice thus depends on the surgeon treating the patient keeping in mind the drawbacks and limitations of each.